Influence of the pilates method on postural balance parameters in older women: An exploratory single-arm trial - Serra, Anna Cláudia Sabino; Orlando, Juliana Botinhon; Scheicher, Marcos Eduardo [UNESP] (Elsevier, 2024)
Background: Human aging is a natural, biological, progressive, dynamic and complex process that involves morphological, physiological and social changes. Alterations such as decreased postural balance increase the risk of falls and exercise has shown benefits. One of the possible exercise modalities for this population is Pilates. Objectives: To investigate the effects of Pilates on parameters of static and dynamic postural balance in older women. Methods: Women aged 60 years or over were evaluated at three time points (pre-training, mid-training, and post-training). Postural balance was assessed using the Short Physical Performance Battery (SPPB), the Timed Up and Go test (TUG), and a force platform. The Pilates exercise protocol consisted of 16 sessions, twice a week, lasting 50 min each. Normality of the data was determined by the Shapiro-Wilk test. Repeated measures ANOVA followed by the Bonferroni post hoc test was used for comparison between assessments. Statistical significance was set at p ≤ 0.05. Results: Fourteen older women were included. Assessment on the force platform revealed no significant differences for most of the variables evaluated. There was a significant difference in SPPB scores and TUG times pre- and post-treatment (p < 0.001). Conclusion: Pilates training significantly improved dynamic postural balance evaluated by the TUG and SPPB but did not significantly improve static balance evaluated by the force platform, although the values have decreased in most assessments.
Keywords: Older adults; Pilates; Postural balance